Assembling of Fluid Filtration System for Quantitative Evaluation of Microleakage in Dental Materials - Javidi, Maryam; Naghavi, Neda; Roohani, Ehsan (Iranian Endodontic Journal, 2008)
INTRODUCTION: There are several methods for evaluating microleakage in dentistry, for example dye or bacterial leakage, electro-chemical methods, radioisotope labeling and fluid filtration. The purpose of this study was to assemble the fluid filtration system for quantitative evaluation of microleakage in dental materials. MATERIALS AND METHODS: The roots were connected to a tube filled with an underwater pressure supply. A bubble was introduced into the water to measure endodontic leakage. A digital camera and professional software were utilized to record and measure the bubble displacement. RESULTS: Our system was constructed successfully and functioned correctly. CONCLUSION: In this pilot study we found this system efficient for the evaluation of microleakage of dental materials.